2021
DOI: 10.1186/s12889-021-10606-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term body mass index changes in overweight and obese adults and the risk of heart failure, cardiovascular disease and mortality: a cohort study of over 260,000 adults in the UK

Abstract: Background Although obesity is a well-recognised risk factor for cardiovascular disease (CVD), the impact of long-term body mass index (BMI) changes in overweight or obese adults, on the risk of heart failure, CVD and mortality has not been quantified. Methods This population-based cohort study used routine UK primary care electronic health data linked to secondary care and death-registry records. We identified adults who were overweight or obese, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Lastly, overweight and obesity were determined using BMI at baseline and we did not take account of changes in BMI over time. We know, however, from previous analyses of BMI trajectory in this study population, and in other obese populations, that BMI of obese individuals does not change significantly over time [ 21 23 ].…”
Section: Discussionmentioning
confidence: 69%
“…Lastly, overweight and obesity were determined using BMI at baseline and we did not take account of changes in BMI over time. We know, however, from previous analyses of BMI trajectory in this study population, and in other obese populations, that BMI of obese individuals does not change significantly over time [ 21 23 ].…”
Section: Discussionmentioning
confidence: 69%
“…In past studies, BMI was examined [ 31 , 34 , 35 ] as a factor related to mortality [ 36 , 37 ] and malnutrition, and mortality was discussed based on BMI measured at a point in time. However, our study showed that by continuously measuring BMI and EI and examining the resulting trajectories and their relationship, instead of treating each parameter as a separate predictor, mortality risks could be identified with more accuracy.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Recent studies from United Kingdom and the United States provide evidence for the reliability of self-reported BMI from self-reported height and weight measurements 39 and that for the vast majority of the population, BMI categories are fairly stable over time. 40 Analyses were limited to only five race/ethnicity categories and five chronic conditions. However, future studies should also look at these patterns for other racial groups and chronic conditions.…”
Section: Discussionmentioning
confidence: 99%